2006
DOI: 10.1038/sj.emboj.7601359
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of Puma and Noxa in dual regulation of p53-mediated apoptotic pathways

Abstract: The activation of tumor suppressor p53 induces apoptosis or cell cycle arrest depending on the state and type of cell, but it is not fully understood how these different responses are regulated. Here, we show that Puma and Noxa, the well-known p53-inducible proapoptotic members of the Bcl-2 family, differentially participate in dual pathways of the induction of apoptosis. In normal cells, Puma but not Noxa induces mitochondrial outer membrane permeabilization (MOMP), and this function is mediated in part by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 54 publications
3
77
2
1
Order By: Relevance
“…The induction of PUMA and NOXA was speculated to be another crucial event mediating the synergistic apoptosis. PUMA and NOXA have been shown to be the transcriptional targets of p53 and essential mediators in p53-induced apoptosis (39)(40)(41)(42). In the current study, we found that both TH-302 and bortezomib can activate p53 and its downstream target gene p21 WAF1/CIP1 in multiple myeloma cells expressing wild-type p53 (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…The induction of PUMA and NOXA was speculated to be another crucial event mediating the synergistic apoptosis. PUMA and NOXA have been shown to be the transcriptional targets of p53 and essential mediators in p53-induced apoptosis (39)(40)(41)(42). In the current study, we found that both TH-302 and bortezomib can activate p53 and its downstream target gene p21 WAF1/CIP1 in multiple myeloma cells expressing wild-type p53 (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…The BH3-only protein Bax, PUMA, and NOXA play important roles in mitochondrial apoptotic pathways induced in p53-dependent and -independent manners (3,(39)(40)(41). Perp, Pig11, and Wig1 are also involved in apoptosis (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, PUMA and NOXA are also upregulated during ER stress, both have been found at the ER, and both play a role in ER Ca 2 þ release (Reimertz et al, 2003;Luo et al, 2005;Rao et al, 2006;Shibue et al, 2006;Kieran et al, 2007;Nickson et al, 2007;Hassan et al, 2008). PUMAmediated apoptosis has been linked to activation of caspase-12 and is reduced by caspase-12 knockdown or deficiency (Shibue et al, 2006).…”
Section: Pathways Leading To Er Stress-induced Apoptosismentioning
confidence: 99%
“…PUMA was shown to induce both caspasedependent and caspase-independent MOMP, with the caspase-dependent pathway proceeding through calpain-associated activation of caspase-12 (Shibue et al, 2006), whereas NOXA led to both cytochrome c release and activation of JNK/p38 mitogen-activated protein kinase (Hassan et al, 2008).…”
Section: Apoptosis and Er Ca 2 þ Release: Bh3 Only Proteinsmentioning
confidence: 99%